Economic Consultative Bodies : Their Origins and Institutional Characteristics - Roy, André (Relations industrielles / Industrial Relations, 1971)
This article reviews "Economic Consultative Bodies : Their Origins and Institutional Characteristics" by Paul Malles, edited by Information Canada.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z